Abnormal and Clinical Psychology / An Introductory Textbook: Second Edition - Bennett Paul (Open University Press, 2006)
This textbook has been extensively updated to include the latest research and therapeutic approaches as well as developments in clinical practice. Acknowledgements, Background and Methods, Introduction, The Psychological Perspective, Biological Explanations and Treatments, Beyond the Individual, Specific Issues, Somatoform Disorders, Schizophrenia, Anxiety Disorders, Mood Disorders, Trauma-Related Conditions, Sexual Disorders, Personality Disorders, Eating Disorders, Developmental Disorders, Neurological Disorders, Addictions, Glossary, References, Index.